TINGKAT PENGETAHUAN TALASEMIA, PENYAKIT MENULAR SEKSUAL DAN KESEHATAN REPRODUKSI PADA REMAJA USIA SEKOLAH MENENGAH PERTAMA - Wratsangka, Raditya; Tungka, Endrico Xavierees; Krishna Murthi, Aditya; Gushaendri, Idman; Shafia, Faiza (Jurnal AKAL: Abdimas dan Kearifan Lokal, 2024)
This PKM Activity aims to determine the level of knowledge of adolescents about thalassemia, sexually transmitted diseases, and reproductive health. The method used in this PKM is material presentation/ counseling and direct interviews using a questionnaire linked to the Google Form application. The results of this PKM activity were obtained as follows; The source of information that plays a dominant role in conveying sexually transmitted infections-HIV/AIDs is the internet, namely 57(53.4%). As many as 76(70.4%) students did not know about thalassemia. Surveys on sexually transmitted diseases/AIDs show that the average junior high school teenager has sufficient knowledge, namely above 50%. Surveys on reproductive health knowledge show that the average junior high school teenager has good knowledge about the physical changes that occur during puberty, including; 1) an Increase in muscle mass (30%), 2) a change in voice (71.8%), 3) hair growth on the face and pubic area (95%), 4) increased sex drive (33.6%). 5) enlarged breasts (17.3%), 6) menstruation started (40.9%). A survey limited to female respondents showed that the level of knowledge about the female reproductive cycle related to the fertile period in junior high school teenagers was around 24 (43.3%) respondents, but 30 (50%) respondents did not know this. The level of knowledge about the fertile period and the possibility of pregnancy occurring in that period are: 1) the response of not knowing was 26 (43.3%), people, 2) immediately after menstruation ended 14 (23.3%), 3) in the middle between two menstruations as many as 14 (23.3%). From the results obtained, it can be concluded that the level of knowledge of junior high school adolescents regarding thalassemia is still very poor, while for sexually transmitted infections and reproductive health, it is at an average level. It is hoped that after participating in PKM, teenagers will have a better level of knowledge than before.